2018
DOI: 10.1123/ijsnem.2017-0352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Duration on Subsequent Appetite and Energy Intake in Obese Adolescent Girls

Abstract: There is a growing interest regarding the effect of exercise on appetite and energy intake in youth. While the role of exercise intensity has been a primary focus of study, the effect of exercise duration on subsequent food intake has not been fully examined in obese adolescents. On three separate mornings in a randomly assigned order, obese adolescent girls (n = 20) aged 12-15 years old were asked to perform a rest session (control, CON) or two cycling sessions for 20 (EX20) or 40 min (EX40) set at their vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The lack of modification in post-exercise absolute EI might be explained by the moderate intensity of the exercise bout. Indeed, while our results are in line with some studies using similar exercise intensities (28,29) , other studies conducted in similar populations reported reduced EI after single bouts of vigorous-intensity exercise (>70 % of maximal capacity) (10,30,31) . This anorexigenic effect of vigorous-intensity exercise in adolescents with obesity has been confirmed in a recent systematic review and metaanalysis (8) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lack of modification in post-exercise absolute EI might be explained by the moderate intensity of the exercise bout. Indeed, while our results are in line with some studies using similar exercise intensities (28,29) , other studies conducted in similar populations reported reduced EI after single bouts of vigorous-intensity exercise (>70 % of maximal capacity) (10,30,31) . This anorexigenic effect of vigorous-intensity exercise in adolescents with obesity has been confirmed in a recent systematic review and metaanalysis (8) .…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown previously in healthy weight boys and girls that ingestion of a mid-morning snack, both before acute exercise and an equivalent period or rest, suppressed hunger and prospective food consumption and elevated fullness compared with exercise and rest conditions with no snack provision (13) . The present study in adolescents with obesity observed no differences in any of the fasting, pre-meal or total daily appetite sensations after exercise inducing an energy deficit, supporting previous studies in adolescents with obesity (28,34) . Our findings extend the present evidence base by demonstrating that subjective appetite is not altered in adolescents with obesity when the Table 2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While most of the studies available so far have focused on the role of exercise characteristics on subsequent nutritional responses, such as its intensity (Thivel et al, 2011(Thivel et al, , 2012 or duration (Masurier et al, 2018;Tamam et al, 2012), only few have questioned its timing in relation to meals.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of exercise, depending on its duration [15,16], intensity [17][18][19], modality [20][21][22] or induced-energy expenditure [23] on the control and regulation of appetite and energy intake have received a lot of attention for the last decade, the impact of exercise-timing remains unclear. Since we recently suggested "Timing" as a third "T" to the FITT exercise prescription method (Frequency, Intensity, Time (duration), and Type of exercise) [1], it seems important to further question the potential effects of the timing of exercise on appetite control to optimize the impact of our interventions on both sides of the energy balance (expenditures and intake).…”
Section: Introductionmentioning
confidence: 99%